First record of Ereymatermes rotundiceps (Termitidae: Nasutitermitinae) as inquiline of Embiratermes neotenicus (Termitidae: Syntermitinae) in the Colombian Amazon - DURAN-BAUTISTA,Ervin Humprey (2022)
ABSTRACT We report, for the first time, the presence of the termite Ereymatermes rotundiceps Constantino, 1991 as an inquiline of the termite Embiratermes neotenicus (Holmgren, 1906) in the Colombian Amazon, and provide new morphometric information on the species. Soldiers of E. rotundiceps were collected in epigeal nests built by E. neotenicus in pastures during the transition from the dry to the rainy season. The association between host and inquiline termites does not seem to be antagonistic, but the relationship between these two species still needs to be clarified.